Effects of Whey Protein Concentrate on the Bioaccessibility and Microstructure of 5-Methyltetrahydrocalcium Folate in Simulated Digestive Environment in Vitro - Yusong ZHANG; Weiran CUI; Zhenyue TANG; Hongyu BAI; Meili SHAO (Shipin gongye ke-ji)
Bioaccessibility is a prerequisite for 5-methyltetrahydrocalcium folate (5-MTHF) to perform their health functions and is susceptible to the influence of food components. Through in vitro simulated digestion, the effects of whey protein concentrate (WPC) on the bioaccessibility of 5-MTHF under various circumstances (concentration, processing technique, gastrointestinal pH, and digesting duration) were examined. The changes of particle microstructure before and after digestion were observed by colloid particle size potentiometer and laser confocal. According to the findings, 5-MTHF could be securely wrapped, shielded by WPC throughout the stomach stage of digestion, and then moved to the small intestine for full release. Additionally, during the digestive process, the bioaccessibility of WPC-5-MTHF tended to rise in all groups. In the meanwhile, several factors such as WPC concentration, WPC processing technique, gastrointestinal pH, and digestion duration had varied effects on the bioaccessibility of 5-MTHF as well as the particle size and potential of WPC-5-MTHF during the digestive process. Among them, the bioaccessibility was 0 and no 5-MTHF was found in any WPC-5-MTHF group throughout the stomach digesting stage. When compared to the 5-MTHF group, the bioaccessibility of the WPC-5-MTHF group improved by 11.1% to 19.61% during the intestinal digestion stage, exhibiting a positive connection trend with the WPC concentration. When compared to the unprocessed treatment group, the bioaccessibility of the ultrasonic, high pressure homogenization groups was reduced by 8.49%, 9.52%, and 8.75%, respectively. At an intestinal pH of 7 and a digestion time of 5 hours, the WPC-5-MTHF group displayed the best bioaccessibility, which was twice as high as that of the 5-MTHF group, at 45.17% and 42.32%, respectively. The results of particle size and zeta potential showed that the WPC-5-MTHF group had smaller particle size, larger absolute value of zeta potential, and the structural changes of WPC-5-MTHF would cause changes in digestibility characteristics. Theoretical support for the use of 5-methyltetrahydrofolate calcium in dairy products is provided by this work.